Analyzing the use of Social Media by Fashion Designers with K-Means and C45 - Abulwafa Muhammad; Sarjon Defit (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2022)
Social media is one part of digital marketing that is used for the development of marketing business products known as social-marketing. The use of social media as social marketing is still managed conventionally and has not implemented business social media. This study was conducted to analyze the clusters and classifications of the use of social media by fashion designers in West Sumatra in marketing their products. This analysis uses the k-Means algorithm and c45 uses the Rapidminer application for the fashion designer industry in West Sumatra. Data is collected from Instagram and Facebook of fashion designers. The data analyzed by K-Means resulted in 3 clusters of social media use, namely 3 less active clusters, 12 active clusters and 1 very active, then classification using the C45 method resulted in a decision tree that described the most and the least in using social media. This study resulted in grouping and classifying variables from whether or not the use of social media in social marketing for the fashion designer industry players in West Sumatra was good or not. The results of this study can be used as a reference for developing integrated marketing for West Sumatra fashion designers.